2022
DOI: 10.3389/fonc.2022.940706
|View full text |Cite
|
Sign up to set email alerts
|

Increased MPO in Colorectal Cancer Is Associated With High Peripheral Neutrophil Counts and a Poor Prognosis: A TCGA With Propensity Score-Matched Analysis

Abstract: BackgroundMyeloperoxidase (MPO) has been demonstrated to be a local mediator of inflammation in tissue damage in various inflammatory diseases. Given its controversial effect on colorectal cancer (CRC), there has been growing interest in investigating the role of this enzyme in CRC. The mechanism underlying MPO activity and CRC progression requires further clarification.MethodsThe expression and function of MPO in CRC were evaluated using TCGA analysis. TCGA, TIMER, and Human Cell Landscape analyses were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…We found that total MPO within the cells was increased at higher concentrations of MPO. During inflammation, levels of MPO are reported to be elevated (33), but there is no data, to our knowledge, regarding local MPO concentrations around neutrophils following degranulation. We hypothesize that upon activation of neutrophils, there is a high concentration of MPO released in their surrounding environment.…”
Section: Discussionmentioning
confidence: 98%
“…We found that total MPO within the cells was increased at higher concentrations of MPO. During inflammation, levels of MPO are reported to be elevated (33), but there is no data, to our knowledge, regarding local MPO concentrations around neutrophils following degranulation. We hypothesize that upon activation of neutrophils, there is a high concentration of MPO released in their surrounding environment.…”
Section: Discussionmentioning
confidence: 98%
“…MPO is a member of the heme peroxidase superfamily and is the most abundant protein expressed by neutrophils. It is reported to generate reactive oxygen species (ROS) leading to DNA damage and mutation inducing carcinogenesis and thus resulting in tissue damage (30). PRTN3 is a serine protease secreted by cells of myeloid lineage and allocated to the cell surface of neutrophils and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,35 In addition to the cell types mentioned above, other immune cell types are also relevant for different diseases. 3641…”
Section: Discussionmentioning
confidence: 99%
“…21,22,35 In addition to the cell types mentioned above, other immune cell types are also relevant for different diseases. [36][37][38][39][40][41] Of note, the described PCR analysis was developed to obtain a rapid overview of the general cellular composition of the immune microenvironment. The method was not designed to discriminate accurately between different functional states or activation profiles of the different immune cell populations.…”
Section: Discussionmentioning
confidence: 99%